2005
DOI: 10.1007/s10822-005-0096-7
|View full text |Cite
|
Sign up to set email alerts
|

Protonation-induced stereoisomerism in nicotine: Conformational studies using classical (AMBER) and ab initio (Car–Parrinello) molecular dynamics

Abstract: A variety of biologically active small molecules contain prochiral tertiary amines, which become chiral centers upon protonation. S-nicotine, the prototypical nicotinic acetylcholine receptor agonist, produces two diastereomers on protonation. Results, using both classical (AMBER) and ab initio (Car-Parrinello) molecular dynamical studies, illustrate the significant differences in conformational space explored by each diastereomer. As is expected, this phenomenon has an appreciable effect on nicotine's energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Nicotine has two main conformers formed as a result of possible free rotation about the two rings connected by the single C–C bond. The gas electron diffraction studies supported by theoretical calculations suggested that the mixture of two conformers consists of two structures with methyl group and the pyridine ring in the equatorial positions of the pyrrolidine ring . However, comparison of the two conformers with the acetylcholine structure indicated that only one of them, with longer N…N distance, is active against the nAChR receptor .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nicotine has two main conformers formed as a result of possible free rotation about the two rings connected by the single C–C bond. The gas electron diffraction studies supported by theoretical calculations suggested that the mixture of two conformers consists of two structures with methyl group and the pyridine ring in the equatorial positions of the pyrrolidine ring . However, comparison of the two conformers with the acetylcholine structure indicated that only one of them, with longer N…N distance, is active against the nAChR receptor .…”
Section: Introductionmentioning
confidence: 98%
“…The gas electron diffraction studies supported by theoretical calculations suggested that the mixture of two conformers consists of two structures with methyl group and the pyridine ring in the equatorial positions of the pyrrolidine ring . However, comparison of the two conformers with the acetylcholine structure indicated that only one of them, with longer N…N distance, is active against the nAChR receptor . The second‐order MP2/6‐31G** and B3LYP/6–31G** calculations have shown that the two nicotine energy minima differ by only ~0.2 kJ mol –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Since nicotinoid agonists’ activity against nAChR depends on the intramolecular N⋅⋅⋅N distance,27 which is conditional on the molecular conformation adopted, getting insight into the molecular and electronic structure, conformational and electronic properties of (−)‐ S ‐cotinine can help to get a better understanding of the molecular recognition mechanisms in nAChR which, in turn, are very valuable for the elucidation of the nature and magnitude of their interactions with the molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…compounds. [23][24][25][26][27][28][29] The chiroptical version of Raman spectroscopy (i.e. Raman optical activity) has been recently applied to study (À)-S-nicotine in a water solution and indicated the presence of the two lower energy conformers in the low-frequency region.…”
Section: Introductionmentioning
confidence: 99%